A Survey of Classification Methods and Techniques for Improving Classification Performance - M, Balasaraswathi; A, Uthiramoorthy (International Journal of Computer Sciences and Engineering, 2019)
This paper surveys the state of the art techniques which have been reviewed to develop the overall classification meth- odology of this research work. The feature selection methods, traditional classification algorithms followed by a brief description of theoretical works on data mining are summarized. The major classification approaches and the techniques which is used for improving classification performance are analyzed. In addition, some important issues affecting classification performance are discussed. In this paper we have gone through the existing work in the area of classification which will allow us to have a fair evaluation of the progress made in the field of Classification.